A Novel CdS/g‐C3N4 Composite Photocatalyst: Preparation, Characterization and Photocatalytic Performance with Different Reaction Solvents under Visible Light Irradiation. Issue 2 (12th July 2016) - Ye, Xiangju; Dai, Xia; Meng, Sugang; Fu, Xianliang; Chen, Shifu
Abstract: CdS/graphtic carbon nitride (CdS/g‐C3 N4 ) hybrid materials were fabricated by thermal polymerization and hydrothermal methods using Cd(CH3 COO)2 2H2 O, thioacetamide, and melamine as precursors. The structural and optical properties of the as‐synthesized samples were investigated by X‐ray powder diffraction, UV–vis diffuse reflectance spectroscopy, scanning electron microscopy, transmission electron microscopy, etc . A coupled system toward the selective oxidation of benzyl alcohol to benzaldehyde and the reduction of nitrobenzene into aniline was used to estimate the photocatalytic performance of CdS/g‐C3 N4 composite photocatalysts under visible light illumination. Results indicate that the CdS/g‐C3 N4 sample exhibits an outstanding photocatalytic performance for selective oxidation of benzyl alcohol and reduction of nitrobenzene. Meanwhile, benzotrifluoride is the best reaction medium among the screened solvents. Further research demonstrates that the selective oxidation of benzyl alcohol to benzaldehyde is induced by the photoexcited holes and the reduction of nitrobenzene into aniline is triggered by the photoexcited electrons. Additionally, the catalyst can be recycled several times without noticeable deactivation. Abstract : CdS/graphtic carbon nitride (CdS/g‐C3 N4 ) hybrid materials were synthesized by thermal polymerization and hydrothermal methods using Cd(CH3 COO)2 2H2 O, thioacetamide, and melamine as precursors. Upon visible light irradiation, a coupled system toward the selective oxidation of benzyl alcohol to benzaldehyde and the reduction of nitrobenzene into aniline was realized by the as‐synthesized photocatalyst. Results indicate that CdS/g‐C3 N4 sample exhibits an outstanding photocatalytic performance for selective oxidation of benzyl alcohol and reduction of nitrobenzene. Further study suggests that the selective oxidation of benzyl alcohol to benzaldehyde is induced by the photoexcited holes and the reduction of nitrobenzene into aniline is triggered by the photoexcited electrons. Additionally, the catalyst can be recycled several times without noticeable deactivation.